Perencanaan Strategis Sistem Informasi dan Teknologi Informasi Pada Perusahaan Retail dengan Pendekatan Jhon Ward and Joe Peppard - Utami Aryanti; Dwi Atmoko (Masoem University, 2021)
PT. Yella Perdana is a retail company engaged in providing computer products in the form of hardware, software, accessories, notebooks, printers in West Java. To be able to face competition in the business world and place the company in a superior position from competitors, an IS/IT strategy is needed. In its implementation, the use of information systems must be supported by a good and appropriate strategic planning of information systems, so that the goals and objectives expected by the company can achieve optimal results.The right IS/IT strategic planning at PT. Yella Perdana is expected to produce a competitive advantage in accordance with the company's resources to support the achievement of company goals.The preparation of IS/IT strategic planning in this study used the Ward and Peppard approach. Assisted by several analytical methods to analyze the company's internal and external business environment such as PEST, SWOT, Porter's Five Force, Value chain, and CSF. This IS/IT strategic planning produces a recommendation for a computer-based application portfolio that can be implemented in accordance with the company's strategy to create an advantage over competitors based on the required information system.